Analisis Manajemen Risiko Dalam Proses Pengambilan Keputusan Persetujuan Bangunan Gedung Pada Dinas Penanaman Modal Dan Pelayanan Terpadusatu Pintu Kota Manado - Mamahit, Susan Imelda; Thambas, Arthur H; Dundu, Ariestides K Torry (Syntax Literate, 2025)
This study aims to examine the application of risk management in the decision-making process of Building Approval (PBG) in Manado City, identify dominant risks that affect service performance, and formulate mitigation strategies that are in line with construction engineering management principles. The research approach is quantitative descriptive-analytical with the support of statistical analysis using primary data from 30 respondents consisting of consultants/applicants, technical assessment teams (TPA/TPT), and DPMPTSP verifiers. Risk identification is carried out through the Risk Breakdown Structure (RBS) method which divides risks into seven categories: technical, administrative, legal, social, environmental, financial, and operational. A total of 28 out of 31 identified risks were declared valid and reliable. The results of the analysis showed nine dominant risks with a high level of severity, including incompatibility with the plan drawings with field conditions, calculations of structures that do not follow SNI 1726:2019 and SNI 2847:2019 standards, overlapping central-regional regulations, limited expert personnel, and low understanding of the applicant of the PBG online system. These risks have an impact on validation delays, technical inconsistencies, and increased costs due to design revisions. Based on the SWOT analysis, the mitigation strategy is in the WO (Weakness–Opportunities) quadrant, which emphasizes the use of external opportunities to improve internal weaknesses through strengthening cross-agency regulations, digitizing the licensing system, improving human resource competence, and effective collaboration between stakeholders. The results of the study confirm that the implementation of integrated risk management can increase the effectiveness, transparency, and accountability of the building licensing system in Manado City in accordance with the principles of good governance.